Pengaruh Vegetasi Mangrove terhadap Keberadaan Bekantan (Nasalis larvatus) di Desa Cemara Labat - Muhamad Tito; Bunda Halang (Biocaster : Jurnal Kajian Biologi, 2026)
Cemara Labat Village is a coastal area located in Kapuas Regency, Central Kalimantan which directly faces the Java Sea and borders Pelampai Village, Batola Regency, South Kalimantan. The village receives enough sediment from the Kapuas River to support the development of mangrove forests. For generations, the people of Cemara Labat Village have managed coastal resources, namely mangrove forests based on traditional traditions known as local wisdom. Mangrove forest vegetation experiences significant dynamics that are very important for the survival of various fauna in it, such as mammals (langurs and proboscis monkeys), fish, shrimp, insects, and even various types of birds. The purpose of this study is to describe the existence of proboscis monkeys based on the population of dominant mangrove species. The research was carried out for six months, from January - June 2025. Data were collected using observation and survey methods. For mangrove observation, it is carried out by making three Observation Sample Plots (PCP) measuring 20 x 500 m, while for proboscis monkey observation by making six observation stations that are made intentionally. Proboscis monkey observation starts at 06.00-18.00 WIB. The results showed INP ≥ 10% of the 6 species found, such as the White Flame (Avicennia marina (Forssk.) Vierh.) 199.99% are included in the medium category (101-200%), Black Flame (Avicennia alba Blume.) is 42.36%, Jeruju (Acanthus ilicifolius L.) is 17.07%, Piai (Acrostichum aureum L.) is 13.39%, Blind (Excoecaria agallocha L.) is 6.70%, and Plepotan (Derris trifoliate) is 5.90% in the low category (0-100%). Eight proboscis monkeys (Nasalis larvatus) were found in the area of the observed object. Although Avicennia spp. dominates the vegetation, the population of proboscis monkeys is relatively small, suggesting that Avicennia spp. mangroves are not the main feed crops for proboscis monkeys and only serve as a migration area.